Out of Sight, Out of Mind: Migration, Entrepreneurship and Social Capital - Jackline Wahba; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
The aim of this paper is to investigate whether return migrants are more likely to become entrepreneurs than non-migrants. We develop a theoretical search model that puts forward the trade off faced by returnees since overseas migration provides an opportunity for human and physical capital accumulation but, at the same time, may lead to a loss of social capital back home. We test the predictions of the model using data from Egypt. We find that, even after controlling for the endogeneity of the temporary migration decision, an overseas returnee is more likely to become an entrepreneur than a non-migrant. Although migrants lose their original social networks whilst overseas, savings and human capital accumulation acquired abroad over-compensate for this loss.
Keywords: L26; O12; O15; 330; Social capital; entrepreneurship; selection; savings